2022
DOI: 10.3390/antibiotics11020247
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Antibiotic Dispensing at Pharmacies According to the WHO Access, Watch, Reserve (AWaRe) Classification in Bangladesh

Abstract: The WHO Essential Medicines List Access, Watch, and Reserve (AWaRe) classification could facilitate antibiotic stewardship and optimal use. In Bangladesh, data on antibiotic dispensing in pharmacies according to the AWaRe classification are scarce. We aimed to explore antibiotic dispensing pattern in pharmacies according to the WHO AWaRe classification to aid pharmacy-targeted national antibiotic stewardship program (ASP). From January to July 2021, we interviewed drug-sellers from randomly selected pharmacies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 35 publications
7
20
4
2
Order By: Relevance
“…Indicaciones no aprobadas relacionados con la prescripción de macrólidos en un grupo de pacientes de Colombia, 2020 (N=9.344) Siria fue mayor el uso de la claritromicina (23). Al considerar estos patrones de uso durante la pandemia de Covid-19, en diferentes estudios se ha informado un mayor empleo de azitromicina (24,25), lo que concuerda con los hallazgos acá registrados. Las dosis diarias definidas por 1.000 personas por día es la medida preferida para comparar el consumo de medicamentos entre países, y comprender mejor los patrones y cantidades utilizadas a nivel nacional, de manera que puedan hacerse intervenciones que optimicen el uso de los antibióticos (13).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Indicaciones no aprobadas relacionados con la prescripción de macrólidos en un grupo de pacientes de Colombia, 2020 (N=9.344) Siria fue mayor el uso de la claritromicina (23). Al considerar estos patrones de uso durante la pandemia de Covid-19, en diferentes estudios se ha informado un mayor empleo de azitromicina (24,25), lo que concuerda con los hallazgos acá registrados. Las dosis diarias definidas por 1.000 personas por día es la medida preferida para comparar el consumo de medicamentos entre países, y comprender mejor los patrones y cantidades utilizadas a nivel nacional, de manera que puedan hacerse intervenciones que optimicen el uso de los antibióticos (13).…”
Section: Discussionunclassified
“…Entre los diferentes antibióticos de este grupo farmacológico, predominó la prescripción de azitromicina, lo que coincide con publicaciones previas en Colombia (41,0 %) 11 , y en pacientes ambulatorios de otros países como México (57,7 %) 20 y Ecuador (55,7 %) 21 , pero contrasta con lo hallado en Malasia, en donde prevaleció el uso de la eritromicina 22 , en tanto que en Siria fue mayor el uso de la claritromicina 23 . Al considerar estos patrones de uso durante la pandemia de Covid-19, en diferentes estudios se ha informado un mayor empleo de azitromicina 24 , 25 , lo que concuerda con los hallazgos acá registrados. Las dosis diarias definidas por 1.000 personas por día es la medida preferida para comparar el consumo de medicamentos entre países, y comprender mejor los patrones y cantidades utilizadas a nivel nacional, de manera que puedan hacerse intervenciones que optimicen el uso de los antibióticos 13 .…”
Section: Discussionunclassified
“…A renowned daily newspaper in Bangladesh named The Daily Star on January 13 in 2020 published an article headlining antibiotics use, sale: who needs prescription? where they investigated the inappropriate and overuse of antibiotics and found that ceftriaxone, a watch group drug, used most frequently by people in Bangladesh (21). This research work also reported the most used 3 rd generation cephalosporin named ceftazidime and ceftriaxone among pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 26, 2022. ; https://doi.org/10.1101/2022.06. 21.22276716 doi: medRxiv preprint It is more challenging to formulate antibiotic dosages for children than for adults. Antibiotic doses must be formulated for achieving optimal effectiveness (13).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…As dispensing practice should differ for different drug classes, specified documentation methods are needed for specific drug classes to ensure obtaining detailed information, which can be used for specific improvements in practice. Studies that focus on antibiotic dispensing have been performed around the globe [16][17][18][19][20][21][22][23][24][25], but mainly aim to identify patterns in dispensing practices, e.g., regarding the type of antibiotic dispensed or over-the-counter dispensing of antibiotics. Such studies seem very relevant to picture general antibiotic use; nonetheless, they might not be as useful in providing specific improvements for community pharmacy practice.…”
Section: Comparison With Literaturementioning
confidence: 99%